Az OVHR modell vizsgálata a magyar közműszolgáltatóknál - Nemeskéri, Zsolt; Sebők, Marianna; Zádori, Iván; Szabó, Balázs (Kultúratudományi Szemle, 2023)
The Hungarian Energy and Public Utilities Regulatory Authority and the Environmental Philosophy, Bioethics and Green Philosophy Research Group of the University of Pécs in the framework of the 2020-2.1.1-ED-2020-00107 project deal with the investigation of theoretical and practical questions of sustainability. Research activities related to the OVHR model also play an important role in the implementation of the project. The OVHR model defines the four key areas (operations, values, human resources, responsibility), the appropriate management of which can result in the sustainable operation of the organisations in the longer term. Based on the OVHR model, our study presents the sustainability-related practices of Hungarian utility providers. In addition to presenting our results and verifying our model, our study shows the main patterns of the key areas of the OVHR model in this special sector are considered to be emphemphasiseding everyday operations and practices and also focus on the relationships can be observed between the key areas and the role of HRD that contributes to the more sustainable operation of the sector's actors.